The Influence of Principals' Leadership on Interpersonal Skills and Teachers' Use of Canva Media at SDN 6 Talang Muandau - Izurani, Izurani; Indra, Musnar; Wahyuni, Molli (Journal of English Language and Education, 2025)
This study aims to determine the effect of principal leadership on interpersonal skills and the use of Canva media by teachers at SDN 6 Talang Muandau. This study uses a quantitative approach with a survey method. The sample in this study were all teachers at SDN 6 Talang Muandau, totaling 16 people. Data collection techniques were carried out by distributing questionnaires to 16 teachers who were respondents in this study and observation sheets. The research instrument includes three variables, namely principal leadership (X), interpersonal skills (Y₁), and use of Canva media (Y₂). Data analysis was carried out using IBM SPSS Statistic 25 through simple linear regression tests and partial t-tests. The results of the study showed that there was a positive and significant influence between principal leadership and teacher interpersonal skills, with a regression coefficient value of 0.984 and a significance value of 0.000 (0.05). In addition, principal leadership also had a positive and significant effect on the use of Canva media by teachers, with a regression coefficient value of 0.651 and a significance value of 0.030 (0.05). From these results, it can be concluded that the quality of the principal's leadership contributes directly to improving teachers' interpersonal skills and encouraging the use of digital media such as Canva in the learning process. This study recommends the importance of increasing the leadership capacity of principals and ongoing training for teachers in utilizing learning technology.